Oleoylethanolamide treatment affects gut microbiota composition and the expression of intestinal cytokines in Peyer’s patches of mice - Di Paola, Monica (Sci Rep, 2018)
The lipid sensor oleoylethanolamide (OEA), an endogenous high-affinity agonist of peroxisome proliferator-activated receptor-α (PPAR-α) secreted in the proximal intestine, is endowed with several distinctive homeostatic properties, such as control of appetite, anti-inflammatory activity, stimulation of lipolysis and fatty acid oxidation. When administered exogenously, OEA has beneficial effects in several cognitive paradigms; therefore, in all respects, OEA can be considered a hormone of the gut-brain axis. Here we report an unexplored modulatory effect of OEA on the intestinal microbiota and on immune response. Our study shows for the first time that sub-chronic OEA administration to mice fed a normal chow pellet diet, changes the faecal microbiota profile, shifting the Firmicutes:Bacteroidetes ratio in favour of Bacteroidetes (in particular Bacteroides genus) and decreasing Firmicutes (Lactobacillus), and reduces intestinal cytokines expression by immune cells isolated from Peyer’s patches. Our results suggest that sub-chronic OEA treatment modulates gut microbiota composition towards a “lean-like phenotype”, and polarises gut-specific immune responses mimicking the effect of a diet low in fat and high in polysaccharides content.